2014
DOI: 10.1007/s11102-014-0558-9
|View full text |Cite
|
Sign up to set email alerts
|

Pons herniation into skull base after cabergoline therapy of giant prolactinoma

Abstract: Some studies have shown that a significant and rapid tumor shrinkage resulting from treatment with cabergoline can occur and it is thought that some complications are related with this tumor regression, as in the presented case.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
3
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 12 publications
1
3
0
Order By: Relevance
“…On the basis of his clinical course, we concluded that the rapid reduction of the tumor by DA therapy, resulting in retraction of brain matter, especially the temporal lobe around the tumor, could have been the mechanism of the epileptic seizures. This mechanism is a known cause of brain herniation with DA therapy for giant PRLomas [8, 9, 11]. The appearance of a hyperintense area in left frontal lobe on T2-weighted images may support our hypothesis of the pathogenic mechanisms of the epileptic seizure in our patient.…”
Section: Discussionsupporting
confidence: 77%
See 2 more Smart Citations
“…On the basis of his clinical course, we concluded that the rapid reduction of the tumor by DA therapy, resulting in retraction of brain matter, especially the temporal lobe around the tumor, could have been the mechanism of the epileptic seizures. This mechanism is a known cause of brain herniation with DA therapy for giant PRLomas [8, 9, 11]. The appearance of a hyperintense area in left frontal lobe on T2-weighted images may support our hypothesis of the pathogenic mechanisms of the epileptic seizure in our patient.…”
Section: Discussionsupporting
confidence: 77%
“…Moles Herbera et al . reported a giant PRLoma showing pons herniation into the skull base caused by tumor shrinkage after DA therapy [11]. In addition, some authors reported cases of frontal lobe herniation as a rare complication of DA therapy (Table 2) [810, 12].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, a case of pons herniation into the clivus after treatment of a giant prolactinoma with cabergoline has been reported. Moles Herbera et al ( 28 ) reported a 59-year-old with a giant prolactinoma treated with cabergoline 1 mg per week. Eighteen months after treatment he presented with left hemiparesis and dysarthria.…”
Section: Discussionmentioning
confidence: 99%